Hepatogenous diabetes: Is it time to separate it from type 2 diabetes?. (31st December 2016) - Orsi, Emanuela; Grancini, Valeria; Menini, Stefano; Aghemo, Alessio; Pugliese, Giuseppe
Abstract: By definition, hepatogenous diabetes is directly caused by loss of liver function, implying that it develops after cirrhosis onset. Therefore, it should be distinguished from type 2 diabetes developing before cirrhosis onset, in which specific causes of liver disease play a major role, in addition to traditional risk factors. Currently, although hepatogenous diabetes shows distinct pathophysiological and clinical features, it is not considered as an autonomous entity. Recent evidence suggests that the failing liver exerts an independent "toxic" effect on pancreatic islets resulting in β‐cell dysfunction. Moreover, patients with hepatogenous diabetes usually present with normal fasting glucose and haemoglobin A1c levels and abnormal response to an oral glucose tolerance test, which is therefore required for diagnosis. This article discusses the need to separate hepatogenous diabetes from type 2 diabetes occurring in subjects with chronic liver disease and to identify individuals suffering from this condition for prognostic and therapeutic purposes.